Understanding the indigenous Chinese concept of suzhi (素质) from an HRM perspective: A conceptual analysis. Issue 2 (7th October 2014) - G. Wang, Greg; Lamond, David; Worm, Verner; Gao, Wenshu; Yang, Shengbin
Abstract : Purpose: – The purpose of this paper is to examine the indigenous Chinese concept of suzhi (素质) with the aim of furthering the development of Chinese human resource management (HRM) research and practice. Design/methodology/approach: – An extensive review of the literature on suzhi, published in the West, as well as in China, is the basis for proffering an organizational-level conceptualization of suzhi in the Chinese context. Findings: – Instead of understanding it as a free-floating signifier, we argue that suzhi can be considered as a criterion-based framework for HRM research and practice. Suzhi research is classified into two major sources – indigenous Chinese and indigenized Western constructs. We further make a distinction between intrinsic and extrinsic suzhi, and analyze a popular set of suzhi criteria, considering de (morality) and cai (talent), while focusing on de in HRM selection (德才兼备, 以德为先). As multilevel and multidimensional framework, suzhi criteria may form different gestalts in different organizations and industries. Research limitations/implications: – From a social cultural and historical perspective, HRM research that incorporates a combination of indigenous and indigenized suzhi characteristics may receive better acceptance by individuals, organizations and the society in the Chinese context. Accordingly, the reconstruction of suzhi into manageable and measurable dimensions can be undertaken for more effective HRM practice in the Chinese context. Originality/value: – The HRM literature is advanced by linking the indigenous suzhi discourse to Chinese indigenous HRM research and practice.